The Impact and effect of caffeine on the improvement of muscle strength of students in the college of physical education and sports at Al-Aqsa University - Dr. Nadir Ismaeel Halawa; Dr. Husham Ali Alaqraa (physical education and sport sciences college for women/ Baghdad University, 2021)
The study aimed to acknowledge the impact of caffeine on the improvement of muscle strength of students in the college of physical education and sports at Al-Aqsa University, the researchers used the descriptive method, and the sample (21 students) were a first-year physical education and sports students. The most important result was that one hour after the caffeine were taken, there was a significant change in the results of the muscle force tests, as follows: For strength endurance, the stomach test had time (30 seconds), the improvement rate was 11.45%. For pressure testing, the rate of improvement was 11.45%. And the pressure of the inclined recline test, the improvement rate was 13.51%, As for the speed, the broad jump test, the improvement rate reached 7.27%, To test the thrust of the medical ball, the improvement rate was 7.91%, As for the maximum strength component of the dead lift test, the improvement rate was 9.53%, and for the knee bending test, the improvement rate was 7.5%. For chest push ups testing, the improvement rate was 10.64%. Caffeine was used as a nutritional supplement containing caffeine anhydrous in an amount of 200 mg, from 2.5 to 3.5 mg/kg each dose of student's weight. Additionally, many previous references that include caffeine were scanned, which our study matched with some of these ones, using the average dose